Development and Testing of the Combined Assessment of Psychiatric Environments: A Patient-Centered Quality Measure for Inpatient Psychiatric Treatment. (March 2015) - Delaney, Kathleen R.; Johnson, Mary E.; Fogg, Louis
BACKGROUND: Inpatient psychiatric treatment satisfaction measures are not constructed from patients' perspective of hospitalization experiences that they deem meaningful and important.OBJECTIVE: To develop and conduct psychometric testing of a measure that evaluates person-centered care on inpatient psychiatric units, the Combined Assessment of Psychiatric Environments (CAPE). The measure is built on a theoretical framework holding that if optimal care is to be achieved, all major stakeholders (patients and staff) need to experience a positive environment.DESIGN: An instrument development design was used to create the patient/staff nurse versions of the CAPE and to test their dimensions. The pilot versions of the CAPE were tested on six inpatient psychiatric units to determine the psychometrics of the staff/patient versions.RESULTS: The overall reliability of both versions of the CAPE (staff/patient) was .91. The test–retest reliability for both versions was significant at the .01 level. Construct validity was established via factor analysis. Criterion-related validity was demonstrated by correlations of the two versions of the CAPE to instruments that were conceptually related.CONCLUSION: The CAPE is a valid and reliable instrument that can be used to examine practice and the patient experience on inpatient psychiatric units. The CAPE highlights that patient-centered environments of care are intertwined with staff experiences of support for their role.